Hidrogéis injetáveis à base de goma guar e carboxietilquitosana reforçados com nanopartículas de vidro bioativo com potencial aplicação na engenharia de tecidos - Ferreira, Carlos Rhamon do Nascimento (2024)
Hydrogels are a class of polymeric materials that constitute a promising application in tissue engineering and regenerative medicine due to their similarities with the natural extracellular matrix of tissues. Injectable hydrogels constitute a subclass of hydrogels that can be applied directly to tissue injury to fill and support tissue regeneration. One way to provide greater mechanical resistance to hydrogels is to add reinforcing agents, such as bioactive glass nanoparticles, which in addition to being biodegradable, biocompatible and osteoconductive, induce the formation of a layer of carbonated hydroxyapatite at the biomaterial/tissue interface. Initially, the guar gum depolymerized by the acid-ethanol treatment was oxidized to different degrees of oxidation (30, 50 and 70%) using sodium periodate and the chitosan was carboxyethylated from the Michael addition reaction with acrylic acid, becoming soluble. in a wide pH range. The main techniques used to characterize polysaccharides and their modifications were: FTIR, 1H NMR and GPC. The obtained bioactive glass nanoparticles had an average size of 138 ± 29 nm, spherical shape with smooth morphology and a uniform size distribution. The formulated hydrogels had gelation times of 37 to 97 seconds, increasing with the presence of bioactive glass. The injectable hydrogels had excellent injectability/syringability without interrupting the flow or obstructing the cannula. The SEM showed that the hydrogels are formed by a porous and interconnected network with average pore values between 123 ± 5 to 356 ± 15 µm and with a porosity of 66.3 ± 1.4 to 87.4 ± 2.1 (%); decreasing their values with the presence of bioactive glass. Degradation studies in PBS showed that the hydrogels showed a slow loss of mass over a period of 28 days (with an average degradation of 30 to 50% of their initial mass) and the swelling of the samples showed controlled values during a period of 180 minutes. (ranging from 30 to 45% of its initial mass). In vitro cytotoxicity assays using two cell lines (fibroblasts and osteoblasts) confirmed the non-toxic and biocompatible nature of the studied formulations. Thus, it is possible to verify that hydrogels have potential application in tissue regeneration, as they show ease in manipulating their studied properties.